Realigning the Sacred and Secular among a Marginalised Population of Caravan Park Residents - Newton, Janice (Australian religion studies review, 2012)
This article addresses calls for qualitative research into the realignment of the sacred and secular among contemporary Western individuals, as well as considering the significance of the economic and social marginality of caravan-park living on this. The 50 Victorian residents interviewed did not exhibit the enhanced spirituality experienced globally among some poor communities. Rather, the sample would seem particularly secular, albeit softened by the persistence of Christian moral codes, and a continued belief in the ineffable. The small minority engaged in active Christian worship reflected the contemporary juxtaposition of postmodern deep feeling and experiences that provide compensatory release, and modern commitment to confirmatory structured ritual or life rules that give assurance. Involvement with New Age ideas appeared relatively superficial. The majority of participants displayed a commitment to individual choice and subjectivisation, and some were engaged with identity-building projects that contained a spiritual element